American Culture and the (Permanent, Global) Cold War (on Terror). (6th May 2020) - Vincent, Jonathan
Abstract: This review-essay considers recent scholarly work that, in contrast to our understanding of the Cold War's demise 30 years ago, examines the lingering practices of permanent militarization that have nonetheless continued to flourish. Focusing especially on the cultural habits that normalize permanent war—a necessary supplement since the Cold War's justifying logics no longer adhere—they together enlarge a picture of the dyadic or double-jointed projects of a transforming military–industrial complex occurring at all manner of points internationally as well as in a range of locales internal to US life, and in ways that are structurally linked. At the heart of that critique is disclosing the way that the adapting discourses of a liberalizing American state downplay and reframe the older, more overt rhetorics of colonialism and imperialism while nonetheless retaining similar expansionist and disciplinary goals. Using the literary and cultural record of those structural adaptations, they document how the twin arms of that coordinated state power worked relentlessly to manage "neocolonial" interventions across the globe, well into the "forever wars" of our own time, as well as, simultaneously, to interfere in and subdue the civil right movement or prosecute the War on Drugs domestically.